PERAN INOVASI PRODUK DALAM MEMEDIASI PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN - Devara, Komang Satya; Sulistyawati, Eka (E-Jurnal Manajemen; Vol 8 No 10 (2019)DO - 10.24843/EJMUNUD.2019.v08.i10.p25, 2019)
The purpose of this study is to explain product innovation plays a role in mediating the effect of market orientation on marketing performance. This research was conducted at the fashion industry UKM in Denpasar City. The number of samples in this study were 50 respondents. The sampling technique is non-probability sampling using the purposive sampling method. Data collection was obtained from the results of questionnaires in the fashion industry SMEs in Denpasar City. Data analysis in this study used path analysis and sobel test. The results of path analysis and sobel test show that product innovation variables play a role in mediating the effect of market orientation on the marketing performance of the fashion industry SMEs in Denpasar City. The results of this study indicate that the better the fashion industry SMEs in Denpasar City make product innovations, the greater the influence of market orientation on marketing performance. Keywords: market orientation, product innovation, marketing performance